On the Origin and Function of the Armenian Article ը - MKRTCHYAN, GARIK (Bulletin of Yerevan University B: Philology, 2021)
The article considers the problem of the origin of Armenian definite article ը. Observations show that the usage of the definite article ը in Armenian is the result of natural laws and inner development of the language. This can also be proved by theabsence of etymological equivalents of this grammatical particle in sister languages of Armenian. The usage of article ը is the result of regular phonetic changes. In consequence of dropping of the final consonant ն, ը of the hidden syllable fulfils thefunction of an article.
Keywords: article, definite article, indefinite article, dialect, hidden syllable, dialect of Van, Mush dialect, phonetis, morphology, morpheme